Ethics on the Laboratory Floor
IX, 230 p.
Keywords: This volume unites ethicists and social scientists to contribute to a new type of technology ethics. Cooperation with scientists makes it possible to anticipate ethical questions and problems at a stage when the technology can still be changed.